The Euro Zone – between Fiscal Heterogeneity and Monetary Unity - Horaţiu DAN (Transylvanian Review of Administrative Sciences, 2014)
In a period in which the functioning of the Euro Zone has generated intense debate, this paper aims at providing a detailed view on one of the main characteristics defining the single currency area: the dichotomy between a unique monetary policy and an almost complete lack of fiscal integration. After analyzing the relationship between fiscal and monetary policies, we iden- tify within the European construction a series of weak points generated by a highly hetero- geneous fiscal environment, arguing that these deficiencies need to be swiftly addressed. Last but not least, we set forth potential solutions that would promote Euro Zone fiscal discipline and would help eliminate asymmetric shocks, thus creating a more uniform economic environment in which Member States enjoy an increased fi- nancial health and in which monetary policy can be more efficiently conducted.